Impact of cardiovascular risk factors on morbidity and mortality in Czech middle-aged men: Pilsen Longitudinal Study - Rosolova, H; Simon, J; Sefrna, F (Cardiology, 1994)
The impact of biological and life-style characteristics measured during baseline examination on 12-year morbidity and mortality of coronary heart disease (CHD), stroke (STR), and malignancies was investigated in an urban population of 3,540 middle-aged men initially free of clinical disease. The following factors enhanced significantly (at the 5% level) the adjusted relative risk ratios: for total mortality age, smoking, and elevated systolic blood pressure; for CHD age, smoking, elevated systolic blood pressure, serum cholesterol levels, and body mass index, and family history (father or mother). Myocardial infarction was positively associated with age, smoking and elevated serum cholesterol levels. For STR age and elevation of both systolic and diastolic blood pressure were risk factors. The relative risk for all malignancies was enhanced by age and smoking. Regular alcohol consumption was associated with a significantly lower risk for all CHD; however, with only marginal significance for myocardial infarction. Higher education was associated with a significantly lower risk of total mortality, all CHD, and myocardial infarction and a marginally lower risk of STR. A high leisure physical activity was negatively (but not significantly) associated with the risk of all end points.
Keywords: Male; kohortové studie; morbidita; longitudinální studie; Neoplasms; Risk Factors; Cohort Studies; Mortality; Česká republika; Adult; dospělí; mužské pohlaví; Czech Republic; kardiovaskulární nemoci; Morbidity; lidé; Humans; rizikové faktory; mortalita; Longitudinal Studies; nádory; Cardiovascular Diseases; lidé středního věku; Middle Aged